The Origins of Islamic Legal Theory (Uṣūl al-Fiqh) - Bakar, Mohd Daud (Intellectual Discourse, 2013)
The question of, and the debate on, the origins of Islamic legal theory continues, largely in the academic circles of Western Islamicists. As for Muslim scholars, they have done little to redress the imbalance. This article presents a summary of the major arguments of Western Islamicists. The arguments are then re-examined to redress any misconceptions about the origins of Islamic legal theory. The ultimate aim is to suggest a new methodology for studying the early legal history of Islam.